The 57th IEEE Semiannual Vehicular Technology Conference, 2003. VTC 2003-Spring.
DOI: 10.1109/vetecs.2003.1207121
|View full text |Cite
|
Sign up to set email alerts
|

A neighbor-table-based multipath routing in ad hoc networks

Abstract: Abstroct--Due to station mobility, the network topology is continuously changing in mobile ad hoc networks. In this paper, we propose a neighbor-tahle-hased multipath routing (NTBMR) protocol to track the dynamic topology changes. Distinguished from prior work on multipath protocols employing disjoint paths, NTBMR does not require the routes to he disjoint. In order to verify the different capabilities against dynamic topology changes for disjoint end non-disjoint multipath routings, we make an attempt to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The protocol stack in MANET is shown in Fig. 2 deals with many issues including the energy conservation, mobility management, reliable transmission and security [29,30]. [1]), portrayed QoS provisioning depends on different organization the board strategies including asset the executives and medium access control (Macintosh).…”
Section: Manetmentioning
confidence: 99%
“…The protocol stack in MANET is shown in Fig. 2 deals with many issues including the energy conservation, mobility management, reliable transmission and security [29,30]. [1]), portrayed QoS provisioning depends on different organization the board strategies including asset the executives and medium access control (Macintosh).…”
Section: Manetmentioning
confidence: 99%
“…This approach allows us to both reuse of paths which become unavailable for a time and avoid by simply treating them as useless, upon interfered, and discarding them. In [17], the theoretical analysis has showed that the route reliability of non-disjoint paths is higher than disjoint paths when the wireless links are unstable. Therefore, in this article, we introduce a new multi-path discovery scheme that can find multiple loop free non-disjoint paths for relay nodes based on modified AOMDV route discovery procedure [18][19][20].…”
Section: Multi-path Routing Protocol Aware Of Iamentioning
confidence: 99%
“…In addition, in most practical networks, using fixed multiple access strategies, such as TDMA and FDMA, cannot meet the strict timeliness requirements of real-time applications since IoT devices may work intermittently. Therefore, random multiple access strategies, e.g., CSMA/CA and so on, are more practical for IoT networks and Industry 4.0 systems [10], [11].…”
Section: Introductionmentioning
confidence: 99%